PSA LEVEL AND ADVERSE EVENTS IN SIXTH AND TENTH SERIES DOCETAXEL CHEMOTHERAPY IN CASTRATE-RESISTANT PROSTATE CANCER (CRPC) PATIENTS - Seputra, Kurnia Penta; Kustono, Andri; Hakim, Muhammad Baihaqy Ibnu (Indonesian Urological Association, 2025)
Objective: This study aims to compare the efficacy of docetaxel on PSA levels and to analyze the adverse events caused by docetaxel. Material & Methods: The study design was retrospective cohort. Participants were prostate cancer patients at Saiful Anwar Hospital who received androgen deprivation therapy with increased PSA level 3 times the nadir or 2 bone lesions or soft tissue lesions > 2cm. PSA levels were assessed monthly. Participants were grouped into 6 and 10 series regimens. Adverse events of nausea, diarrhea, alopecia, SGOT SGPT abnormailties, creatinine abnormalities, anemia, and neutropenia were observed. Statistical analysis was performed using a differential T-test. Results: A total of 32 participants were involved. The PSA levels between 6 and 10 series groups were as follows: 1st month (142.2 vs 28.24 ng/mL,p=0.000), 2nd month (101.78 vs 16.98 ng/mL,p=0.001), 3rd month (472.35 vs 13.95 ng/mL,p=0.439), 4th month (120.64 vs 4.0 ng/mL,p=0.180), 5th month (64.325 vs 24.6 ng/mL, p=0.015), 6th month (41.915 vs 20.7 ng/mL,p=0.497). Adverse events in the 6 and 10 series regimens were nausea (25% vs 81.25%), diarrhea (37.5% vs 50%), alopecia (6.25% vs 43.75%), SGOT SGPT abnormalities (25% vs 56.25%), creatinine abnormalities (6.25% vs 37.5%), anemia (18.75% vs 31.25%), leukocytosis (6.25% vs 0%), and neutropenia (25% vs 12.5%). Adverse events in 6 series regimen began to occur in 3rd series with 1 participant experiencing nausea, and the most were 3 participants experiencing diarrhea in 6th series. Adverse events in 10 series regimen began to occur in 4th series with 1 participant experiencing nausea, 1 participant experiencing SGOT SGPT abnormalities, 1 participant experiencing diarrhea, and the most were 4 participants experiencing nausea in the 9th series. Conclusion: The 10 series of docetaxel chemotherapy is not superior to 6 series. Adverse events are more prominent in the 10 series. Keywords: Docetaxel, PSA, adverse events.